EVOLUTION AND PROBLEM OF THE COLLOQUIAL FRENCH IN THE 21ST CENTURY - Samid Nasirov Ahir (Research Retrieval and Academic Letters, 2023)
As one of the international languages, French, like other languages, is constantly evolving, being innovated and enriched by words borrowed from other languages. Considered as the driving force of the Francophone community covering Europe, the Americas, Africa and even a number of Asian countries, French contains different characteristics, being a written language and a spoken language. Thus, the present article is concerned with reporting the language used by young French speakers in their daily conversations, emphasizing the influence of social networks used extensively by the younger generation on spoken French, and moreover addressing other factors that cause the evolution of this multi-secular language spoken, taught, learned and used all over the world. In this article, norms that are not respected by all users of this language for various reasons are also highlighted, some sources of negative impact on this language are also detailed through linguistic arguments.